Hoya yingjiangensis (Apocynaceae, Asclepiadoideaea), a new campanulate-flowered species from Yunnan, China - Zhang, Jingfeng; Bai, Lin; Xia, Nianhe; Peng, Zeqiu (Phytotaxa, 2015)
Hoya yingjiangensis (Apocynaceae, Asclepiadoideae) from Yunnan Province, China, is described and illustrated. This species possesses a large campanulate corolla, but is distinguished from all the other species of Hoya with similar corollas by the peduncle annual, deciduous, and the inflorescence single-flowered. The provisional IUCN assessment of ‘Data Deficient’ for H. yingjiangensis is provided.